The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1002/mrc.2237
|View full text |Cite
|
Sign up to set email alerts
|

Deuterium isotope effects on 13C chemical shifts of nitromalonamide

Abstract: The OH chemical shift of the enol form of nitromalonamide is found at 18.9 ppm both in DMSO-d(6) and in DMF-d(7) indicating a very strong hydrogen bond. The OH chemical shift is insensitive to temperature changes. Contrary to the large OH chemical shift, a small two-bond deuterium isotope effect of 0.135 ppm due to deuteration at the OH position is found at the enolic carbon. This is confirmed by density functional theory calculations. The observed effects are interpreted as due to an equilibrium between ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…Series 1 is; Data from Refs. [ 5 , 37 , 42 , 43 ] series 2 citrinin [ 44 ]; series 3 is data for mono anions of succinic acid [ 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…Series 1 is; Data from Refs. [ 5 , 37 , 42 , 43 ] series 2 citrinin [ 44 ]; series 3 is data for mono anions of succinic acid [ 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…The 1 H chemical shift of acetyl acetone enol ( 3 ) is experimentally determined as 15.5 ppm and the anisotropy effect estimated as 0.4 ppm [ 12 ] Here, we use the value 15 ppm as a lower limit for strong O–H···Y hydrogen bonds. The upper value 19 ppm is taken from nitromalonamide enol ( 4 ) [ 31 ]. Larger shifts are considered to correspond to systems with very strong hydrogen bonds.…”
Section: Introductionmentioning
confidence: 99%
“…The 15 N NMR data is also a powerful tool for the confirmation of hydrazo forms according to the splitting of the exchangeable proton upon nitrogen atom in hydrazo form . Another way to confirm the predominant tautomeric form is carbon‐13 splitting via partial deuteration (for current research work, see later).…”
Section: Resultsmentioning
confidence: 99%
“…One of the most distinguished works about deuterium isotope effects on 13 C chemical shifts have been reported by Hansen et al , who worked on deuterium isotope effects on chemical shifts in intramolecular hydrogen‐bonded systems, especially resonance assisted hydrogen bonding . In those cases, it has been shown that the isotope effect may be transmitted across the hydrogen bonds and may affect the chemical shifts in hydrogen‐bonded systems .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation